The Effect of Current Ratio, Debt to Equity Ratio, BOPO, and GDP Growth on Return on Assets with Moderation of Firm Size in PT Pelabuhan Indonesia (Persero) Period 2018-2022 - Febriyani Syafitri; Gos Ishak; L.M. Samryn (Journal of Social Research, 2023)
The objective of this study is to analyze the impact of various financial indicators on the Return on Assets (ROA) at PT Pelabuhan Indonesia (Persero) between 2018 and 2022. The research adopts a quantitative approach and utilizes the Ordinary Least Square (OLS) method, with data processing conducted using Eviews 13. The findings reveal the financial performance of PT Pelindo one year post-merger, indicating that the Debt to Equity Ratio (DER) and ROA have experienced an increase of 0.06% and 20.85%, respectively. On the other hand, the Current Ratio (CR) and BOPO have both decreased, with a decline of 37.25% and 0.18%, respectively. Hypothesis testing results demonstrate that the individual factors, including CR, DER, BOPO, and GDP growth, do not exert a significant influence on ROA. Furthermore, when considered together, their combined impact remains statistically insignificant. Interestingly, the study finds that the Firm Size has a moderating effect, enhancing the influence of CR, DER, BOPO, and GDP Growth on ROA. This suggests that the size of the firm plays a role in strengthening the relationship between these financial ratios and the company's overall profitability. This quantitative research sheds light on the financial dynamics of PT Pelabuhan Indonesia (Persero) following its merger. While specific financial indicators show changes, they do not significantly affect ROA individually or collectively. However, the interaction of Firm Size with the aforementioned ratios demonstrates a noteworthy correlation with ROA, highlighting the importance of considering firm size when analyzing financial performance.